2017
DOI: 10.4314/bajopas.v10i1.45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of isolated Lupeol from stem bark of <i>Diospyros mespiliformis </i>Horsch (Ebenaceae) against some microbial pathogens

Abstract: Powdered stem bark of plant material (1000g) of Diospyros mespiliformis was extracted with hexane using Soxhlet apparatus and concentrated on a water bath at 60 0 C. The extract was later subjected to column chromatography techniques using gradient elution in which various fractions were obtained and monitored using thin layer chromatography. The structure of the isolated compound were suggested by 1D and 2D spectroscopic analysis and by direct comparison of the data obtained with those reported in literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several studies have been undertaken to isolate bioactive compounds from the leaves, roots, stem, and bark. As a result, several secondary metabolites have been isolated, primarily from chemical constituents, such as terpenoids, naphthoquinones, phenolics, and coumarins [4,[11][12][13][14]. No previous study has yet comprehensively reviewed the traditional uses, phytochemistry, pharmacological activities, and In Vivo animal investigations of D. mespiliformis.…”
Section: Traditional Usesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been undertaken to isolate bioactive compounds from the leaves, roots, stem, and bark. As a result, several secondary metabolites have been isolated, primarily from chemical constituents, such as terpenoids, naphthoquinones, phenolics, and coumarins [4,[11][12][13][14]. No previous study has yet comprehensively reviewed the traditional uses, phytochemistry, pharmacological activities, and In Vivo animal investigations of D. mespiliformis.…”
Section: Traditional Usesmentioning
confidence: 99%
“…Additionally, Mohamed et al [14] isolated lupeol (27), betulin (24), betulinic acid (25), and lupenone (26) from the stems and bark of D. mespiliformis. Anas et al [13] and Adzu et al [61] have reported the isolation and identification of lupeol (27) from the stem bark of D. mespiliformis. Diosquinone (2) and plumbagin (12) were also isolated from the roots of D. mespiliformis by Lajubutu et al [64].…”
Section: Isolated or Tentatively Identified Compounds From D Mespilif...mentioning
confidence: 99%
See 1 more Smart Citation
“…Asiatic acid (Figure 1) has been shown to possess antibacterial activity against E. coli (MIC = 24 ± 4 μg/ml; MBC = 36 ± 4 μg/ml) (W. Liu, Liu, & Mong, 2015) values ranging from 0.9 to 15.6 μg/ml, which closely compared with the positive reference (kanamycin sulphate) with a MIC range of 1.9--3.9 μg/ml. Lupeol and its derivatives isolated from the stem bark of Diospyros mespiliformis Horsch (Ebenaceae) were effective against S. aureus and E. coli with a MIC = 6.25-12.5 μg/ml (Anas et al, 2017).…”
Section: Therapeutic Roles Of Pentacyclic Triterpenes and Urolithiasismentioning
confidence: 99%